T-Cell Leukemia/Lymphoma 1 (TCL1): An Oncogene Regulating Multiple Signaling Pathways - Paduano, Francesco; Gaudio, Eugenio; Mensah, Afua A.; Pinton, Sandra; Bertoni, Francesco; Trapasso, Francesco (Frontiers in Oncology, 2018)
Almost thirty years ago, Carlo Croce’s group discovered the T-Cell Leukemia/Lymphoma 1A oncogene (TCL1A or TCL1). TCL1 protein is normally expressed in fetal tissues and early developmental stage lymphocytes. Its expression is deregulated in chronic lymphocytic leukemia (B-CLL) and most lymphomas. TCL1 plays a central role in lymphomagenesis as a co-activator of AKT kinases and other recently elucidated interacting protein partners. These include ATM, HSP70 and TP63, which were all confirmed as binding partners of TCL1 from co-immunoprecipitation experiments utilising endogenously expressed proteins. The nature of these interactions highlighted the role of TCL1 in enhancing multiple signaling pathways, including PI3K and NF-κB. Based on its role in the aforementioned pathways and, despite the lack of a well-defined enzymatic activity, TCL1 is considered a potential therapeutic target for TCL1-positive hematological malignancies. This perspective will provide an overview of TCL1A and its interacting partners.​